THE EFFECTIVENESS OF USING SMARTPHONE IN LEARNING ENGLISH AT SMA NEGERI 3 BUKITTINGGI - Lestari, Fadiah; Eliza; Darmawati (Jurnal Kiprah Pendidikan, 2023)
This article aims to reveal the effectiveness of using Smartphones in learning English. The problem of the research was students werelessed motivated by the old learning media, students felt bored and lessed interested in learning through lecturedAnd lastly, studentswere sometimes embarrassed to asked directly to the teacher and prefer smartphones. Therefore, researcher was conducted a research at SMAN 3 Bukittinggi to found out whether the uses of smartphones was effective or not for learning English. This research was quantitative. The researcher used simple random sampling to determine the sample because it uses one way to pull out the lottery. The researcher was chose one of the five classes as the sample. The sample in this research were 36 students of class X E4. The data collection technique in this research was documentation in the form of student scores. The results showed that the use of smartphones was effective in learning English. The percentage of students was between 61 – 80% with the mean score calculated as 78,89with an effective assessment quality. This means that the data proves that the use of smartphones is effective in learning English in class X E4 SMAN 3 Bukittinggi.